Elements Of Qualification In The Leadership Construct Of Special Education Headmasters In Malaysia - et. al., Tumisah binti Akim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The issue of workload of special education teachers arises due to five factors such as teachers, students, facilities, curriculum and also the leadership of head teachers. However, the leadership factor of the head teacher is the most important factor in the realization of this issue. There are studies that have found that head teachers play an important role in shaping the direction of school organization and teacher welfare. This factor is also one of the main factors in ensuring job satisfaction of teachers in schools. Among all the elements related to the leadership of head teachers, the element of their qualifications is also one of the causes of the issue of teacher workload. This qualitative study was conducted to detail the qualification elements of headmasters in their leadership practice in the integration special education program (PPKI). This study involved 11 coordinators of the program in the state of Johor, Malaysia. The findings of this study can be used as a reference for future researchers related to the study of special education leadership.